2012
DOI: 10.1002/jhm.1962
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and suboptimal pharmacologic prophylaxis and delayed mobilization but not morbid obesity are associated with venous thromboembolism after total knee arthroplasty: A case‐control study

Abstract: BACKGROUND:The FDA‐approved dose of low‐molecular‐weight heparin (LMWH) may not provide adequate thromboprophylaxis in morbidly obese patients after total knee arthroplasty (TKA). Suboptimal dosing, delayed initiation, and overreliance on mechanical methods may also limit the effectiveness of thromboprophylaxis.OBJECTIVE:We explored the associations between the type of thromboprophylaxis, obesity, time of mobilization, and undergoing bilateral TKA on development of symptomatic venous thromboembolism (VTE) afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…84 Early postoperative mobilisation can reduce relative VTE risk by 65%. [85][86][87] Conversely, an increased duration of anaesthesia (3.5+ hours) has been associated with an almost four times increased overall VTE risk in bilateral knee arthroplasty patients (7.5% vs. 30.2%). 83 Notably, bilateral simultaneous knee arthroplasty itself is associated with an increased VTE risk compared to unilateral knee arthroplasty (up to four times increased VTE risk and 80% increased PE risk), irrespective of time to mobilisation.…”
Section: Other Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…84 Early postoperative mobilisation can reduce relative VTE risk by 65%. [85][86][87] Conversely, an increased duration of anaesthesia (3.5+ hours) has been associated with an almost four times increased overall VTE risk in bilateral knee arthroplasty patients (7.5% vs. 30.2%). 83 Notably, bilateral simultaneous knee arthroplasty itself is associated with an increased VTE risk compared to unilateral knee arthroplasty (up to four times increased VTE risk and 80% increased PE risk), irrespective of time to mobilisation.…”
Section: Other Influencing Factorsmentioning
confidence: 99%
“…83 Notably, bilateral simultaneous knee arthroplasty itself is associated with an increased VTE risk compared to unilateral knee arthroplasty (up to four times increased VTE risk and 80% increased PE risk), irrespective of time to mobilisation. 85,88 Interestingly, the type of anaesthesia may also infuence VTE risk: regional anaesthesia has been reported to carry a lower VTE risk than general anaesthesia; consequently it is often recommended in guidelines and commonly used in practice. 17,51,89,90 A recent study reported that East Asian patients experience very little to no symptomatic VTE following hip and knee arthroplasty, suggesting the value of using routine thromboprophylaxis is debatable in East Asia.…”
Section: Other Influencing Factorsmentioning
confidence: 99%
“…84 Early postoperative mobilisation can reduce relative VTE risk by 65%. [85][86][87] Conversely, an increased duration of anaesthesia (3.5+ hours) has been associated with an almost four times increased overall VTE risk in bilateral knee arthroplasty patients (7.5% vs. 30.2%). 83 Notably, bilateral simultaneous knee arthroplasty itself is associated with an increased VTE risk compared to unilateral knee arthroplasty (up to four times increased VTE risk and 80% increased PE risk), irrespective of time to mobilisation.…”
Section: Other Influencing Factorsmentioning
confidence: 99%
“…83 Notably, bilateral simultaneous knee arthroplasty itself is associated with an increased VTE risk compared to unilateral knee arthroplasty (up to four times increased VTE risk and 80% increased PE risk), irrespective of time to mobilisation. 85,88 Interestingly, the type of anaesthesia may also infuence VTE risk: regional anaesthesia has been reported to carry a lower VTE risk than general anaesthesia; consequently it is often recommended in guidelines and commonly used in practice. 17,51,89,90 A recent study reported that East Asian patients experience very little to no symptomatic VTE following hip and knee arthroplasty, suggesting the value of using routine thromboprophylaxis is debatable in East Asia.…”
Section: Other Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation